The Level of Knowledge and Skills of Special Education Teachers in Teaching with the use of Learning Through Play Method - Munirah Mokhtar; Mohd Hanafi Mohd Yasin; Mohd Mokhtar Tahar (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2019)
Children construct knowledge through a meaningful play. Playing is a norm for each child; hence they are more inclined to learn through play. Children’s playing activities have to be significantly planned by teachers to obtain a quality product. Therefore, this study was conducted to identify the level of knowledge and skills in teaching with the use of learning through play method. The research samples consisted of 44 teachers from 9 schools with the Integrated Special Education Programme in the district of Kinta Selatan, Perak, Malaysia. This quantitative research used survey through a questionnaire that was adapted from Norhaya Isa. The questionnaire had 3 sections which were teachers’ demography, the level of knowledge in teaching using the learning through play method, and the level of skills in teaching using the learning through play method. The research findings were analysed descriptively using the Statistical Package for the Social Sciences (SPSS) Version 22.0. A pilot study was conducted and the coefficient value Alpha Cronbach was high which was 0.937. A descriptive analysis of the mean scores showed that the teachers’ levels of knowledge and skills were high. In conclusion, the research findings showed that teachers’ level of knowledge and skills in implementing teaching and learning through the learning through play method is vital in producing successful special needs pupils. Therefore, teachers need to improve their knowledge as well as to vary their skills in using the various methods of teaching and learning.